Akibat Hukum Objek Hak Atas Tanah yang Sertipikatnya Cacat Hukum - Wa Ode Yulni Farida (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This study discusses errors in land title certificates and legal remedies for victims. This study examines the legal consequences of defective land title certificates and legal remedies for affected parties. The method used, this type of research is normative juridical. The results of the study indicate that land title objects with defective certificates such as SHM 99/Laiba dated 06/07/2021 covering an area of ​​8,102 m² can have legal consequences due to errors in the procedure for submitting documents that do not match the actual land conditions. Inconsistencies in measurement, mapping, and/or area calculations can result in the certificate being invalid, in accordance with the Regulation of the Head of the National Land Agency of the Republic of Indonesia Number 3 of 2011. Communities affected by inaccurate land certificate mapping can sue the State Administrative Agency, the issuing agency, or the State Administrative Court to cancel the certificate.